Challenges in Predicting the Filtration Performance of a Novel Sewn Mask: Scale-up from Filter Holder to Mannequin Measurements - Audrey J. Dang; Benjamin M. Kumfer; J. Tyler Bertroche; Jane Olson Glidden; Christopher R. Oxford; Udayabhanu Jammalamadaka; Mary Ruppert-Stroescu; Alexander R. Scott; Jason A. Morris; Connie Gan; Jesse Hu; Bradley King; et al. (Aerosol and Air Quality Research)
Abstract Novel designs and materials for filtering face-piece respirators (FFRs) have been disseminated in response to shortages during the COVID-19 pandemic. Since filtration efficiency depends on particle diameter and air face velocity, the relevance of material filtration or prototype fit data depends on test conditions. We investigate whether characterizing a material in a filter holder at a range of face velocities enabled precise prediction of the filtration performance of a novel sewn mask design. While larger particles (> 500 nm) are more relevant for inhalation exposure to respiratory emissions, we compare this mask and a N95 FFR (as a control) with smaller particles more similar to those in the N95 test method. Sewn from sterilization wrap, our mask (sealed to a mannequin head with silicone) filters 85 ± 1% of 136 nm particles (NaCl, 85 L min−1) and passes quantitative fit tests for 4 of 6 volunteers, representing intermediate protection between a surgical mask and N95 FFR. Filter holder material measurements overpredict the sewn mask’s filtration efficiency by 8.2% (95% CI 7.4–9.1%) (136 or 200 nm). While testing flat material in a filter holder enables comparison between materials, filtration performance does not precisely scale-up from filter holder to mannequin tests. Testing full prototypes at relevant conditions is crucial if an improvised design is intended as a substitute for a commercial surgical mask or FFR.